Sodium glucose cotransporter 2 inhibitors as diuretic adjuvants in acute decompensated heart failure: a case series. (31st May 2020) - Griffin, Matthew; Riello, Ralph; Rao, Veena S.; Ivey-Miranda, Juan; Fleming, James; Maulion, Christopher; McCallum, Wendy; Sarnak, Mark; Collins, Sean; Inzucchi, Silvio E.; Testani, Jeffrey M.
Abstract: Aims: Diuretic resistance is common in acute decompensated heart failure (ADHF). When loop diuretic monotherapy is ineffective, thiazides are often recommended as adjunctive therapy, but these agents have many side effects and are associated with worsened survival. In contrast, sodium glucose cotransporter 2 inhibitors (SGLT‐2i's), initially developed as glucose‐lowering medications for type 2 diabetes, improve heart failure outcomes. A candidate contributory mechanism for this benefit is their diuretic effects. We sought to describe the safety and efficacy of SGLT‐2i's as loop diuretic adjuvants in ADHF. Methods and results: We retrospectively analysed patients who received adjuvant SGLT‐2i therapy between August 2016 and June 2018 at Yale‐New Haven Hospital. Thirty‐one patients comprised the cohort, 58% of whom had type 2 diabetes. Compared with the 24 h prior to SGLT‐2i initiation, average weight loss improved (1.0 ± 2.2 kg, P  = 0.03 at Day 1; 1.7 ± 4.9 kg, P  = 0.08 at Day 2; and 2.1 ± 5.6 kg, P  = 0.06 at Day 3), as did urine output (3.7 ± 2.0 L, P  = 0.002 at Day 1; 3.4 ± 1.7 L, P  = 0.02 at Day 2; and 3.1 ± 1.7 L, P  = 0.02 at Day 3) while loop diuretic dosing remaining stable. Creatinine remained unchanged during the 3 days after initiation, as did blood pressure and the incidence of hypokalaemia ( P  = NS for all). Conclusions: In this cohort of patients with ADHF, SGLT‐2i's improved weight loss, urine output, and diuretic efficiency without worsening of creatinine, potassium, or blood pressure. Further study of SGLT‐2i's as a loop diuretic adjuvant is warranted.